The role of Kano Emirate Council in managing ethnic and religious conflict in Kano State-Nigeria - Ahmed Aliyu,; Ravichandran Moorthy,; Nor Azizan Idris, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Conflict and security scholars have identified ethnic and religious conflicts as one of the main causes of insecurity in Nigeria the African most populous country. One of the states in which these twin conflicts have been occurring is Kano state that incidentally is also the most populous state in the country. Hausa/Fulani ethnic group whose religion is Islam dominates the state that has a current estimated population of over ten million. However, owing to its background as the commercial nerve centre of the northern region, the state has attracted substantially Christian immigrants from the southern parts of the country. Unfortunately, the relationship between the host Muslim Hausa/Fulani and their Christian immigrants especially the Igbos over the years have been characterized by series of conflicts arising from ethnic and religious acrimonies. Against this backdrop, this paper examines the role of Kano Emirate Council in the management of these conflicts. The study is based on a qualitative research method with secondary data obtained through review of related published materials. Finding of the study revealed that, Kano Emirate Council plays significant role in managing ethnic and religious conflicts in the state on informal basis. On the backdrop of this finding, this paper concludes that management of Kano state security which is often threatened by ethno-religious conflicts can be improved with the reintegration of the Emirate Council into the security management framework.